A Cost-Efficient RGB Laser-Based Visible Light Communication System by Incorporating Hybrid Wavelength and Polarization Division Multiplexing Schemes - Xiang-Peng, CAI (Frontiers in Physics, 2021)
Visible light communication (VLC) has been proven a promising technology to counter the limitations of radio frequency (RF) communication technology such as high interference and high latency issues. VLC offers high bandwidth as well as immunity to interference from other electromagnetic spectrums. Due to these features, VLC can be an excellent solution for biomedical and healthcare applications for transmission of body sensor signals and other crucial patient information. In this work, a highly efficient VLC system is designed to transmit six channels, with each one carrying 10 Gbps of data, over a 500 m optical fiber link and a 200 cm VLC link. To make the VLC system cost effective, simple and efficient on-off keying (OOK) (non-return to zero) is used as the encoding scheme. Moreover, to further enhance the capacity and bandwidth of the proposed VLC system, hybrid wavelength division multiplexing (WDM) and polarization division multiplexing (PDM) schemes are incorporated by using red, green, and blue lasers. The reported results show the successful transmission of all channels (6 × 10 Gbps) over 500 m optical fiber and 200 cm of VLC link.